An electrogenic redox loop in sulfate reduction reveals a likely widespread mechanism of energy conservation - Duarte, Américo G. (2019)
The authors would like to thank Manuela M. Pereira for helpful discussions on liposome experiments and for provision of the ActC structure prior to publication, and Miguel Teixeira for use of the dual-wavelength OLIS spectrophotometer. This work was financially supported by Fundacao para a Ciencia e Tecnologia (Portugal) through fellowships SFRH/BPD/84607/2012 (to A.G.D.) and SFRH/BPD/92537/2013 (to D.L.), grants PTDC/BIA-MIC/6512/2014 and PTDC/BIA-MIC/2723/2014 (to I.A.C.P.) and R&D units UID/Multi/04551/2013 (Green-IT) and LISBOA-01-0145-FEDER-007660 (MostMicro) cofunded by FCT/MCTES and FEDER funds through COMPETE2020/POCI. Funding by the WWTF (VRG15-007 to F.L.S.), BBSRC UK (Grant K00929X to T.A.C.), and the European Union's Horizon 2020 research and innovation programme (Grant agreement no. 810856) is also acknowledged.